2014
DOI: 10.1080/15321819.2014.952443
|View full text |Cite
|
Sign up to set email alerts
|

HBV and HIV Coinfections among Intending Blood Donors in Port Harcourt, Nigeria

Abstract: HBV is a major public health concern as it afflicts an estimated 350 million people worldwide. Studies are crucial and necessary to give us a better understanding of the epidemiology of the diseases in developing countries. A clearer picture of HBV/HIV prevalence in Africa is important in order to better educate the population and control these epidemics. This study estimated the seroprevalence of HBV/HIV coinfections among intending blood donors in Port Harcourt, Nigeria. In this cohort study, we collected bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
4
4
5
Order By: Relevance
“…According to Tessema et al (2010), in a study that included patients aged 41 to 50, the condition was more prevalent; this conclusion is consistent with ours. These most recent findings were consistent with our earlier research in Ibadan, Nigeria (Okonko et al, 2012), which found a higher frequency in people over 40. This observation, however, differs from studies we conducted in Port Harcourt (Abeni et al, 2020) and Ugheli, Delta State, Nigeria (Ogbodo et al, 2015), which found greater prevalences in the age group >26 years.…”
Section: Discussionsupporting
confidence: 93%
“…According to Tessema et al (2010), in a study that included patients aged 41 to 50, the condition was more prevalent; this conclusion is consistent with ours. These most recent findings were consistent with our earlier research in Ibadan, Nigeria (Okonko et al, 2012), which found a higher frequency in people over 40. This observation, however, differs from studies we conducted in Port Harcourt (Abeni et al, 2020) and Ugheli, Delta State, Nigeria (Ogbodo et al, 2015), which found greater prevalences in the age group >26 years.…”
Section: Discussionsupporting
confidence: 93%
“…1, 93 HIV patients were tested for the presence of HBsAg of which 7( 7.5%) of them were positive to the HBsAg. The outcome from this study was higher than a previous study carried out by Baeka et al [13] in which 5.1% was recorded and that of Okonko et al [14] in which 6.1% was recorded in the same city. This may be attributed to the increase in some social habits such as body piercing, tattoo making which has become on the increase in recent times in Port Harcourt.…”
Section: Discussioncontrasting
confidence: 82%
“…Generally, as several studies reported and anticipated in different parts of the world, such co-infection differences could be due to differences in geographic regions, types of risk groups and the means of exposures involved [21,22]. The sero-prevalence rates of HIV-HCV co-infection in this study was 2.8% which is similar to other studies from different parts of the country with prevalence ranging from 2-6% [23][24][25][26].…”
Section: Discussionsupporting
confidence: 81%